Morphology Characterization of Ten Lytic Bacteriophages from Different Family Targeting Klebsiella pneumoniae - Abeer Amen Baqer; Yip Chee Wai; Norefrina Shafinaz Md Nor; Siti Noor Adnalizawati Adnan (Universiti Putra Malaysia, 2024)
Indexed by Scopus